Profile of Pneumopathic Elderly Persons Admitted to a Pulmonary Rehabilitation Center - Melo-neto, João Simão De; Stroppa-marques, Ana Elisa Zuliani; Gomes, Fabiana De Campos (Universidade do Estado do Rio Janeiro, 2016)
AbstractIntroduction: Pneumopathies are defined as a group of respiratory diseases. Physiotherapy centers are a conventional treatment option which can help prevent and treat various pulmonary conditions.Objective: To characterize elderly persons with pneumopathies admitted for pulmonary rehabilitation.Methods: 84 elderly persons were admitted for pulmonary rehabilitation. Patients diagnosed with pulmonary disease and aged ≥60 years were included in the study. The following variables were analyzed: gender, age, marital status, profession, medical diagnosis, main medical complaint, associated diseases, and cardiovascular risk factors.Results: The most common lung disease is chronic obstructive pulmonary disease (COPD) (26.2%). Women showed a greater association with asthma [odds ratio (OR)=5.875; p=0.010]. Dyspnea was the most prevalent main complaint among this population (50%). Among the main complaints, difficulty walking was more associated with men (OR=2.85; p=0.055). Strokes were the main disease most commonly associated with pneumopathies (12.1%). Women had a greater association with other diseases (OR=5.34, p=0.068), especially when two diseases were presented simultaneously with lung disease (OR=2.32, p=0.041). Among the risk factors, physical inactivity (OR=3.33), alcohol consumption (OR=0.046) and history of smoking (OR=3.00) were significantly associated with men, while depression (OR=5.67) was significantly associated with women. Women exhibited a 3.28 greater association between allergies and pneumopathies than men (p=0.013). The practice of physical activity was more associated with women (OR=3.89; p=0.03). Osteoporosis was more prevalent among elderly women with pulmonary disease (OR=10.75; p<0.0001), and was also significantly associated with a history of smoking (OR=4.31; p=0.009).Conclusion: The most frequent diagnosis, main complaint and associated disease were COPD, dyspnea and strokes, respectively. Elderly woman exhibited a greater association with the diagnosis of bronchial asthma, and more diseases associated with lung disease. Physical inactivity, difficulty walking, and a history of alcohol consumption and smoking are more associated with men, while depression, the presence of allergies, regular physical activity and osteoporosis are more associated with women. Thus, the results demonstrate that these individuals have specific characteristics.

ResumoIntrodução: Pneumopatias são definidas como grupo de doenças respiratórias. Centros de fisioterapia surgem como tratamento convencional que contribui para prevenir e tratar variadas condições pulmonares. Objetivo: Caracterizar idosos com pneumopatias admitidos para reabilitação pulmonar.Métodos: A amostra foi composta por 84 pacientes admitidos para reabilitação pulmonar no departamento de fisioterapia cardiopulmonar de uma clínica escola. Pacientes com diagnóstico de doença pulmonar e idade ≥60 anos foram incluídos no estudo. As seguintes variáveis foram analisadas: sexo, idade, estado civil, profissão, diagnóstico médico, queixa principal, doença associada, e fatores de risco cardiovascular.Resultados: A pneumopatia mais comum foi doença pulmonar obstrutiva crônica (DPOC) (26,2%). Mulheres mostraram maior associação com asma [Odds Ratio (OR)=5,875; p=0,010]. Dispneia foi a queixa principal mais prevalente na população (50%). Entre as queixas principais, dificuldade de deambular foi mais associada com homens (OR=2,85; p=0,055). Acidente vascular cerebral (AVC) foi a doença principal mais associada com pneumopatias (12,1%). Mulheres tiveram maior associação com outras doenças (OR=5,34, p=0,068), especialmente, quando apresentaram mais que dois quadros simultaneamente com a pneumopatia (OR=2,32, p=0,041). Entre os fatores de risco, a inatividade física (OR=3,33), o consumo de álcool (OR=0,046) e o histórico de tabagismo (OR=3,00) foram significativamente associados ao sexo masculino, enquanto depressão (OR=5,67) ao feminino. Mulheres apresentaram 3,28 mais associação entre alergias e pneumopatias que os homens (p=0,013). A prática de atividade física foi mais associada com o sexo feminino (OR=3,89; p=0,03). Osteoporose foi mais prevalente em mulheres idosas com doença pulmonar (OR=10,75; p<0,0001), e também significativamente, enquanto associada ao histórico de tabagismo (OR=4,31; p=0,009).Conclusão: O diagnóstico, a queixa principal e a doença associada mais frequentes foram DPOC, dispneia e AVC, respectivamente. Idosas apresentam maior associação com diagnóstico de asma brônquica e mais doenças associadas à pneumopatia. Sedentarismo, dificuldade de deambular, etilismo e histórico de tabagismo são mais associados ao sexo masculino, enquanto que depressão, presença de alergias, prática de atividade física e osteoporose, ao feminino. Assim, os resultados demonstram que esses idosos apresentam características específicas.
Perfil de idosos pneumopatas admitidos em centro de reabilitação pulmonar
Keywords: Health Profile; Lung Diseases; Epidemiology.; Perfil de Saúde; Pneumopatias; Epidemiologia.